Encephalic Schistosoma japonicum resembles brainstem neoplasm: Case report and literature review - Wu, Kang; Zhao, Hong Yu; Shu, Kai; Lei, Ting; Zeng, Liang (Frontiers in Neurology, 2022)
Encephalic schistosomiasis is a rare and severe parasitic disease caused by granuloma formation around ectopic eggs that migrate to the brain. We present a rare case of a pseudotumoral form of Schistosoma japonicum in the brainstem that was initially misidentified as a malignant tumor. The patient presented with intermittent headaches, diplopia, and left limb weakness. Neurological examination revealed hypoesthesia of the left lower limb, limitation of right eye abduction, and decreased muscle strength of the left upper limb. The cerebrospinal fluid tested positive for antibodies against S. japonicum. After standard treatment for schistosomiasis, the patient achieved complete remission. This case highlights that encephalic schistosomiasis can occur in the brainstem and resemble a neoplasm on magnetic resonance imaging. Once diagnosed, however, complete remission is achievable by non-invasive medical treatment.